Ishwar Chandra Vidyasagar: Ideas and Teachings - Dubey, Karnika (International Journal of Psychosocial Rehabilitation, 2021)
Ishwar Chandra Vidyasagar was a prominent social reformer, philanthropist, writer, educator, and Sanskrit Pandit of Bengal. Various notable social reforming activities are maintained by Ishwar Chandra Vidyasagar. The advancement of women is also maintained properly with the involvement of Vidyasagar. Widow Remarriage act is also sanctioned by him, which is treated as an effective success of Vidyasagar as a social reformer. He can play a crucial role in maintaining educational rights for all students, even for Non-Brahmin Hindus. He can redesign the educational system of India, especially in Bengal. Administrative changes in education are maintained by him